2019
DOI: 10.1002/gea.21730
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing past terraced agrarian landscapes in the Ebro valley: The deserted village of Torrentejo in the Basque Country, Spain

Abstract: The historical agrarian landscape features of the deserted medieval village of Torrentejo (Ebro Valley, southern Basque Country, Rioja Alavesa region) are presented here. This study relies on analyses of agricultural lands on terraces and, secondarily, of domestic occupation, funerary spaces, and of a medieval church. An archaeological excavation was carried out around the church, covering 800 m 2 , and exposing more than 2 m of archaeological deposits. The detailed study of 6 ha of terraced land made use of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…
Figure 1.Map of the Mediterranean, with the location of study areas presented in this article: A) Boğsak, Turkey; B) Urla, Turkey; C) Naxos, Greece; D) Catalonia, Spain; E) Galicia, Spain. Previous studies include: 1) southern Greece (Foxhall et al 2007); 2) Kea (Whitelaw 1991); 3) Lesvos (Schaus & Spencer 1994; Kizos & Koulouri 2006); 4) Kythera and Antikythera (Krahtopoulou & Frederick 2008; Bevan et al 2013); 5) southern France (Harfouche 2007); 6) Cyprus (Wagstaff 1992); 7) Galicia, north-west Spain (Ballesteros-Arias et al 2009; Ferro-Vasquez et al 2019); 8) Israel (Davidovich et al 2012; Porat et al 2018, 2019); 9) Jordan (Kuijt et al 2007; Beckers et al 2013); 10) Crete (Betancourt & Hope Simpson 1992); 11) Murcia, south-east Spain (Puy & Balbo 2013); 12) Catalonia, north-east Spain (Boixadera et al 2016); 13) Pyrenees, France (Rendu et al 2015); 14) Ebro Valley, Spain (Quirós-Castillo & Nicosia 2019) (figure by T. Kinnaird).
…”
Section: Introductionmentioning
confidence: 99%
“…
Figure 1.Map of the Mediterranean, with the location of study areas presented in this article: A) Boğsak, Turkey; B) Urla, Turkey; C) Naxos, Greece; D) Catalonia, Spain; E) Galicia, Spain. Previous studies include: 1) southern Greece (Foxhall et al 2007); 2) Kea (Whitelaw 1991); 3) Lesvos (Schaus & Spencer 1994; Kizos & Koulouri 2006); 4) Kythera and Antikythera (Krahtopoulou & Frederick 2008; Bevan et al 2013); 5) southern France (Harfouche 2007); 6) Cyprus (Wagstaff 1992); 7) Galicia, north-west Spain (Ballesteros-Arias et al 2009; Ferro-Vasquez et al 2019); 8) Israel (Davidovich et al 2012; Porat et al 2018, 2019); 9) Jordan (Kuijt et al 2007; Beckers et al 2013); 10) Crete (Betancourt & Hope Simpson 1992); 11) Murcia, south-east Spain (Puy & Balbo 2013); 12) Catalonia, north-east Spain (Boixadera et al 2016); 13) Pyrenees, France (Rendu et al 2015); 14) Ebro Valley, Spain (Quirós-Castillo & Nicosia 2019) (figure by T. Kinnaird).
…”
Section: Introductionmentioning
confidence: 99%
“…Samples from earthworks can be directly dated using radiocarbon or optically stimulated luminescence (OSL) methods (e.g. Beckers et al 2013;Porat et al 2018;Quirós-Castillo & Nicosia 2019), although ecofacts, soils and sediments are liable to similar problems to those affecting artefact-based dating. Material within earthworks can be disturbed through postdepositional processes, which may be virtually impossible to recognise using standard archaeological methods-particularly when studies rely on just one (or a few) quantitative age estimates, or dates from an exposed profile.…”
Section: Introductionmentioning
confidence: 99%
“…One of the best examples comes from the deserted village of Torrentejo (Bastida, Araba), located by the Ebro river. There, a geoarchaeological study, similar to the one carried out at Tobillas, has revealed a sequence of agricultural terraces built in the Early Middle Ages to cultivate the steep hillslopes (Quirós Castillo & Nicosia 2019; Narbarte-Hernández et al 2020). Two key points from that study are particularly relevant to the current discussion.…”
Section: Discussionmentioning
confidence: 87%